Defense mechanisms in plants. Proteins related to pathogenicity - Menéndez, Eduardo (2020)
Since their origins, vascular land plants have coexisted with a wide variety of bacteria and fungi. When insects appeared, they also maintained a close relationship with them, taking on a big role with the arrival of flowering plants in the early Cretaceous period. The different evolutionary processes have led to the development of a series of interspecific interactions; some of them beneficial for both parties, such as the various pollination mechanisms throu- gh insects in many plant species. At the same time, other types of interactions have emerged with species capable of producing severe diseases in different sections of the plant. This evolutionary pressure with the inability of a defense offered by locomotion, and the lack of a defense system based on antibodies, have been the main responsible for the appearance of com- plex defense mechanisms in plants, many times rapid and effective against aggressive species, and sometimes not. The pathologies manifestation in plants depends on complex interactions between host-pathogen, which is an indicator of joint evolution. Thus, the exquisite regula- tion of aggression/defense mechanisms and the corresponding selectivity recognizing external aggressors, may explain the distinct sensitivity of various species or even different varieties within the same species. For some time now, researchers have shown great interest in cer- tain proteins synthesized by a plant when attacked by a pathogenic microorganism. Since they appear in pathological conditions, they have been named Pathogenesis-related (PR) proteins.